2022
DOI: 10.3390/nu14010207
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and Increased Risk of Adverse Outcomes in Elderly Patients Undergoing Elective Colorectal Cancer Surgery: A Case-Control Study Nested in a Cohort

Abstract: Background: Malnutrition increases worse outcomes during hospital admission for elective colorectal cancer (CRC) surgery in older adults. Methods: This work was designed an observational, monocentric, case-control study nested in a cohort of patients undergoing elective surgery for CRC disease at the Hospital Universitario de la Ribera (HULR) (Alzira, Valencia, Spain) between 2011 and 2019. The study considered patients with a CONUT score in the range of moderate to severe malnutrition (>4 points), with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 25 publications
4
15
0
2
Order By: Relevance
“…In addition to inflammation, the roles of nutrition status in the occurrence and development of CRC could not be ignored ( 7 , 8 ). On one hand, CRC cells affect the absorption and utilization of nutrients through inflammation and metabolic processes, making patients with CRC are prone to malnutrition ( 25 , 26 ). On the other hand, due to the gastrointestinal symptoms, which affect the appetite and eating, most of the patients with CRC have varying degrees of malnutrition risk ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inflammation, the roles of nutrition status in the occurrence and development of CRC could not be ignored ( 7 , 8 ). On one hand, CRC cells affect the absorption and utilization of nutrients through inflammation and metabolic processes, making patients with CRC are prone to malnutrition ( 25 , 26 ). On the other hand, due to the gastrointestinal symptoms, which affect the appetite and eating, most of the patients with CRC have varying degrees of malnutrition risk ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study preliminarily illustrated the clinical guidance of the CONUT score as a reliable nutritional screening tool. Similarly, CONUT has been demonstrated to have good prognostic value in cancers and other infections [ 35 , 55 , 56 ]. Although the exact mechanism is uncertain, this association may be explained by the nutritional and immune-related parameters in CONUT [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…For nutritional assessment, we used GLIM criteria, which were born as a result of a consensus of several international organizations for a definition of malnutrition [ 6 ]. Several studies reported malnutrition rates in CRC patients from 20% to 37%, depending on the tool used to assess nutritional status [ 1 , 19 , 20 ]. Other studies showed that malnutrition can affect up to 60% of these patients [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%